Pengaruh Efikasi Diri, Kepuasan Kerja, dan Komitmen Profesional terhadap Kesejahteraan Subjektif Guru SD-SMP Nasima Kota Semarang G - Arya Dwi Bagaskara; Mohammad Fauzan (Journal Of Administration and Educational Management (ALIGNMENT), 2024)
The research aims to analyze and explain the influence of teacher efficacy on subjective well-being, the influence of job satisfaction on subjective well-being, and how professional commitment influences the subjective well-being of Nasima Semarang Elementary and Middle School teachers. This research is a type of explanatory research. The sample for this research was 88 teachers from Nasima Elementary School and Middle School, Semarang City. The data collection method was a Google form questionnaire distributed to all respondents. Next, the data was processed using SPSS version 26. For data analysis, instrument testing was carried out by carrying out validity and reliability tests, Testing the model via the F test, determination test (R²), and hypothesis test (t-test). Research findings on teacher self-efficacy have a positive effect on subjective well-being; job satisfaction has a positive impact on subjective well-being; Professional commitment hurts subjective well-being. In conclusion, subjective well-being is influenced by self-efficacy and job satisfaction. Therefore, school leaders in policies related to teacher management must provide space for teachers to increase self-efficacy by sending teachers to attend higher levels of education and involving teachers in various workshops. To build self-efficacy and a sense of self-satisfaction for teachers through creating a conducive environment and school and school organization to create a sense of happiness for teachers. Keywords: Job Satisfaction, Professional Commitment Subjective Well-being, Teacher Self-Efficacy